Analisis Kadar Mineral Natrium dan Kalium Pada Daging Buah Nanas (Ananas comosus (L) Merr) di Kota Palu - Sada, Nurjayanti Abdullah; Rahman, Nurdin; Supriadi, Supriadi (Universitas Tadulako, 2014)
Mineral is inorganic component which is in the human body. The needs of mineral for the body can be obtained by consuming fruits. Pineapple (Ananas comosus (L) Merr) is one of fruits contains mineral such as potassium (K) and sodium (Na). the objective of the research was to analysis the mineral level (Na and K) contained in pineapple flesh that spread out in Palu City. The analysis of Na and K mineral level used flame photometry analysis. The research result show that pineapple Cayenne varieties (common pineapple) contains sodium mineral as much 3.71 mg/kg and potassium as much at 376 mg/kg. The pineapple Queen varieties (Bogor pineapple) contains mineral sodium as much as 2.41 mg/kg and potassium as much as 198 mg/kg.